2019
DOI: 10.1016/j.jnoncrysol.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser micro-patterning of optical properties and functionalities in novel photosensitive silver-containing fluorophosphate glasses

Abstract: Silver-containing glasses are promising candidates for photonic applications, due to the potentiality of spectroscopic properties of silver nanoclusters (NC's) and/or silver metallic nanoparticles. In this framework, silvercontaining fluorophosphate glasses are candidates with a strong potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These structures can withstand annealed processes from 100 to 350 °C for 3 h compared to the current standard for data storage of 80 °C . Laser-written AgNCs@glass have also been used for the fabrication of super-resolved nanostructures, optical grating, optical switching, micropolarizer, filter, ring resonator, and interferometer (Figure J), display, optical recording/erasing, waveguide, volume holography, frequency converter, and photowritable glass fibers (Figure K). ,,,,, The fabricated structures are highly stable and show outstanding tolerance against temperature, aging, and humidity. ,,, Structures show superior photostability because they do not loose fluorescence even after continuous irradiation of blue light (intensity 100 kW/cm 2 ) for hours.…”
Section: Dlw Of Agncs In Glassmentioning
confidence: 99%
“…These structures can withstand annealed processes from 100 to 350 °C for 3 h compared to the current standard for data storage of 80 °C . Laser-written AgNCs@glass have also been used for the fabrication of super-resolved nanostructures, optical grating, optical switching, micropolarizer, filter, ring resonator, and interferometer (Figure J), display, optical recording/erasing, waveguide, volume holography, frequency converter, and photowritable glass fibers (Figure K). ,,,,, The fabricated structures are highly stable and show outstanding tolerance against temperature, aging, and humidity. ,,, Structures show superior photostability because they do not loose fluorescence even after continuous irradiation of blue light (intensity 100 kW/cm 2 ) for hours.…”
Section: Dlw Of Agncs In Glassmentioning
confidence: 99%
“…To the best of our knowledge, this is the first time that remobilization of the silver reservoir is used to develop periodic structures. As discussed by de Castro et al, [ 68 ] the capability to remobilize the silver reservoir was believed to originate from the presence of highly co‐mobile ions such as fluorine and alkaline ions in silver‐doped oxyfluoride phosphate glasses. In our work, we have shown that the presence of barium ions, in majority in contrast to the potassium, promotes the remobilization of the silver reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the strong luminescence in silver containing glasses is related to the presence of silver species (32,33). The luminescence of silver entities such as isolated ions, pairs and clusters have been widely studied in various glass and in particular in phosphate glass compositions (19,(32)(33)(34)(35)(36). It has been demonstrated that the luminescence of silver ions and silver cluster can lead to broad emission in the whole visible range for main excitation bands located between 200 nm to 400 nm depending on the silver species.…”
Section: Physical-chemical Propertiesmentioning
confidence: 99%